THERMODYNAMIC STUDY OF HEAT RECOVERY POWER PLANT USING ORGANIC RANKINE CYCLE - FAJAR NUGROHO (NIM : 13105015); Pembimbing : Dr.Ir. Prihadi Setyo Darmanto, MUHAMMAD
With the increase of fuel price,. various conservation effort has been proposed to increase fuel consumption efficiency. Heat recovery can be applied for tool or engine which is emitting heat during its operation to increase efficiency of fuel consumption. GensetÃ‚Â’s exhaust gas is one of heat emition which can be recovered as a heat source for Organic Rankine Cycle to generate electricity. Three organic fluid have been chosen as working fluid which are R-123, R- 113 and R-141b. Those working fluids are analyzed at isentropic efficiency of turbine between 0,7-0,9 with air-cooled and water-cooled cooling system. Calculation is performed by assuming 0,15 MPa as a pressure drop in heat recovery boiler and 0,02 MPa as a pressure drop in condensor. For air-cooled cooling system analysis, assumption is taken for minimum and maximum ambient temperature to be 24 oC and 30 oC respectively. Considering environmental, financial, and thermal performance issues, it is suggested to use R-123 as working fluid and air-cooled condenser. For ambient temperature of 30 oC and isentropic efficiency of turbine = 0,7, the generated additional power = 414,73 kW and the percentage of power improvement = 4,76%. Higher performance achieved with the decrease of ambient temperature and the increase of isentropic efficency of turbine.